O lobby indo-americano no Congresso Americano e o Acordo Nuclear Civil de 2008 - Gabriel, João Paulo Nicolini (2019)
This dissertation aims to analyze the actions of ethnic interest groups within the United States foreign policy formulation. In order to do so, it was listed as a case study the performance of the Indian diaspora during the Congressional negotiation process in the United States of the Civil Nuclear Agreement of 2008. Through a bibliographical review and interviews, this objective study is to understand diasporas as political actors interested in the lack of specific agendas through an analysis of a community still little studied in Brazil. This research was divided into three main axes: (i) systematizing the characteristics of the performance of ethnic interest groups in US foreign policy; (ii) analysis of the socio-economic profile of the Indo-American community; and (iii)observation of the conduct of the Indian Diaspora within the US Congress during the nuclear agreement negotiations. In conclusion, the limitations of these interest groups and the circumstances that would make their successes were presented